2011
DOI: 10.3832/ifor0586-004
|View full text |Cite
|
Sign up to set email alerts
|

Towards harmonization of forest deposition collectors - case study of comparing collector designs

Abstract: In recent years the harmonization of methods in the frame of the International Co-operative Programme on Assessment and Monitoring of Air Pollution Effects on Forests (ICP Forests) operating under the UNECE Convention on Long-range Transboundary Air Pollution (CLRTAP) has been intensified. Among the C-actions of the FutMon project (LIFE07 ENV/D/000218; 2009-2010) the C1-Dep-22(SI) action was established with the goal to harmonize and develop the deposition monitoring procedures and sampling methods. The sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The mixed forest site was equipped with eight systematically distributed, fixed-funnel collectors (0.23 m in diameter), installed 140 cm above ground level. In addition, throughfall was collected using ten systematically distributed gutter collectors (3-m long tube, 4-cm in diameter, with three, 87-cm long and 0.9-cm wide slits in lines), with the upper portion installed 0.60 m above the forest floor, draining directly into polyethylene tanks, which were used as collection containers (Zlindra et al 2011). The total sampling area in the 0.25 ha plot was 0.52 m 2 (the receiving area of each funnel collector was 415 cm 2 and of each gutter 185 cm ).…”
Section: Collection Of Rainfall Partitioning Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mixed forest site was equipped with eight systematically distributed, fixed-funnel collectors (0.23 m in diameter), installed 140 cm above ground level. In addition, throughfall was collected using ten systematically distributed gutter collectors (3-m long tube, 4-cm in diameter, with three, 87-cm long and 0.9-cm wide slits in lines), with the upper portion installed 0.60 m above the forest floor, draining directly into polyethylene tanks, which were used as collection containers (Zlindra et al 2011). The total sampling area in the 0.25 ha plot was 0.52 m 2 (the receiving area of each funnel collector was 415 cm 2 and of each gutter 185 cm ).…”
Section: Collection Of Rainfall Partitioning Componentsmentioning
confidence: 99%
“…To achieve a higher spatial representativeness of the throughfall measurements and to improve canopy interception estimates in forests with a large canopy heterogeneity, a higher number of throughfall collectors should be used (Zlindra et al 2011). In addition, the rainfall pattern must be considered when selecting the type and number of collecting devices, since the coefficient of variation increases with decreasing throughfall depth (Zimmermann et al 2010).…”
Section: Canopy Interception In Relation To Rainfall Characteristicsmentioning
confidence: 99%
“…In the LIFE+ FutMon project, a harmonisation experiment is cur rently being carried out, in which national deposition samplers are compared with standardised deposition samplers on forest monitoring plots throughout Europe. A pre liminary paper on this experiment is pu blished in this journal (Zlindra et al 2011).…”
Section: Data Comparabilitymentioning
confidence: 99%
“…Comparability and meaningful interpretation of data derived from long-term monitoring across time require representative measurements based on harmonized methods and a statistically sound design (Clarke et al 2010;Cools and de Vos 2011;Ferretti 2010Ferretti , 2011Ferretti et al 2014. Within this context, the spatial representativity and comparability of atmospheric deposition measurements are crucial issues -for exposure and effect assessments Erisman et al 2003;Lorenz and Granke 2009;Žlindra et al 2011). Clarke et al (2010) found large differences in results of different types of technical samplers and that several factors might influence the measurements, among them the number and surface area of samplers used as well as their placing in the stands and the extent of the area equipped with collectors.…”
Section: Introductionmentioning
confidence: 99%